The Addition of Pumpkin Flour Impacts the Functional and Bioactive Properties of Soft Wheat Composite Flour Blends - Durim Alija; Remigiusz Olędzki; Daniela Nikolovska Nedelkoska; Agata Wojciechowicz-Budzisz; Gafur Xhabiri; Ewa Pejcz; Eljesa Alija; Joanna Harasym (Foods)
Growing interest in functional food ingredients has led to the exploration of pumpkin flour as a nutritional enhancer in wheat-based products. This study investigated the impact of pumpkin flour incorporation (0–20%) on soft wheat flour blends’ technological and bioactive properties. The comprehensive analysis included granulometric distribution, techno-functional properties (WHC, WAC, WAI, WSI, SP, OAC), pasting characteristics (RVA), gel texture (TPA), rheological behaviour (frequency sweeps), colour parameters, and bioactive compounds (TPC, DPPH, ABTS) in both water and ethanol extracts. Pumpkin flour addition systematically modified blend properties, with higher fine particle content (13.26% < 80 μm), enhancing water interaction capabilities (WHC increased from 2.52 to 3.56). Pasting behaviour showed reduced peak viscosity (2444.0 mPa·s to 1859.5 mPa·s) but enhanced gel structure stability, evidenced by increased storage modulus (112.7 Pa to 1151.0 Pa) and reduced frequency dependence. Colour parameters showed progressive darkening (L* 91.00 to 84.28) and increased yellow-orange intensity (b* 10.13 to 27.13). Bioactive properties improved significantly, with TPC increasing up to 0.57 mg/1 g DM and 0.34 GAE mg/1 g DM in water and ethanol extracts, respectively, accompanied by enhanced antioxidant activity. Pumpkin flour incorporation successfully enhanced both functional and bioactive properties of wheat flour blends, with particle size distribution and water interactions serving as fundamental determinants of technological functionality, while contributing to improved nutritional value through increased bioactive compounds.